Use of controlled writing to develop the language proficiency of first year college commerce students - Marcaida, Josefina B. 1949- (1977)
This paper proposed the use of controlling writing for college Freshman English, geared to the needs of freshman Commerce students. The proposed materials consisted of writing activities using controlled to free-writing techniques. The instructional materials presented in this paper are progressively sequenced.
"May, 1977."
Vita.
Thesis (M.A.T.English as a Second Language)--University of the Philippines, Diliman.
Keywords: Written communication -- Study and teaching (Higher) -- Philippines -- Angeles City (Pampanga); English language -- Study and teaching (Higher) -- Philippines -- Aids and devices; English language -- Composition and exercises; Teaching -- Philippines -- Angeles City (Pampanga) -- Aids and devices